Using our voices, losing our bodies: Michael Brown, Trayvon Martin, and the spirit murders of Black male professors in the academy. Issue 2 (4th March 2017) - Johnson, Lamar; Bryan, Nathaniel
Abstract: The recent deaths of Michael Brown, Trayvon Martin, and other Black males have generated new civil rights urgencies in Black communities and spirited academic discourses in higher education regarding the educational and social plight of Black males in America. Connecting the deaths of Black males to our lived experiences in the academy, we use a text messaging performative writing style to demonstrate how Black males are not only gunned down in the streets of America by police but also are metaphorically gunned down in the academy. That is to say, white colleagues and students attempt to use what we call the bullet of rejection, the bullet of silencing, and the bullet of disrespect to destroy us and our academic agenda. We conclude with a call to action for teacher education programs as a way to deepen their understanding of the racialized experiences of Black males in the academy and Black males in America.